"The Ingholt Archive. Data from the Project 'Archive Archaeology: Preserving and Sharing Palmyra's Cultural Heritage through Harald Ingholt's Digital Archives'". (25th October 2021) - Bobou, Olympia; Miranda, Amy C.; Raja, Rubina
Starting in the 1920s and into the 1970s, the Danish archaeologist Harald Ingholt (1896–1985) created a vast collection of sculpture, architecture, and epigraphy from Palmyra, Syria (first to third centuries AD). His paper archive contains 2, 347 so-called archive sheets, which include photographs, transcriptions of inscriptions, stylistic observations and dating, provenance and collection information, and bibliography. In 2012 the archive was digitized by Professor Rubina Raja and the Palmyra Portrait Project . An in print, commented edition of the archive is underway, but this publication serves to make the archive sheets openly available as a research resource and a starting point for future research on Palmyrene art and epigraphy, the history of excavations in the Middle East, twentieth century collecting practices, and cultural heritage preservation in Syria.